Resúmenes de novedades - Foro Internacional, Revista (Foro Internacional, 2024)
TYLER JOST. 2024. Bureaucracies at War: The Institutional Origins of Miscalculation. Cambridge, Reino Unido: Cambridge University Press. RICHARD TUCK. 2024. Active and Passive Citizens: A Defense of Majoritarian Democracy. Editado por Stephen Macedo. Princeton, N.J.: Princeton University Press. ELIZABETH N. SAUNDERS. 2024. The Insiders’ Game: How Elites Make War and Peace. Princeton, N.J.: Princeton University Press. HONGSHAN Li. 2024. Fighting on the Cultural Front: U.S.-China Relations in the Cold War, Nueva York: Columbia University Press. JOHANNES GERSCHEWSKI. 2023. The Two Logics of Autocratic Rule. Cambridge, Reino Unido: Cambridge University Press. JOSEPH STIGLITZ. 2024. The Road to Freedom: Economics and the Good Society. Nueva York: W. W. Norton & Company. OLIVIER ROY. 2024. The Crisis of Culture: Identity Politics and the Empire of Norms. Traducido por Cynthia Schoch y Trista Selous. Londres: Hurst & Company. DAN HONIG. 2024. Mission Driven Bureaucrats: Empowering People to Help Government Do Better. Nueva York: Oxford University Press ERNST WOLFGANG BÖCKENFÖRDE. 2024. El surgimiento del Estado como proceso de secularización. Traducción de Carlos Pérez Crespo. Madrid: Trotta. JESSICA ALCÁZAR YLIZALITURRI. 2024. El feminismo en la política exterior de México. Ciudad de México: Flacso México.